(3JejjR GdHjY Yf ZjQg ef GdYbhO,GdJaGhV,EHQGe GdHjY hUhQg,GdHjhY GdOhdjI hGdEdcJQhfjI hGdeYdheGJjI,MeGjI GdeSJgdc,fbd GdedcjI,GdVeGf,GdhaGA GdEdcJQhfj,aSN GdYbOs - (3eMeO MSfj(B, (3efUhQs ((3GdEScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2006)
(3eGgjI YbO GdHjY(B-(3GdTF GdeHjY(B-(3GdCgdjI hGdefY ef GdTQGA(B-(3MeGjI GdeSJgdc aj GdHjYs
Keywords: (3GdHjYs; (3GdHjY GdEdcJQhfjs; (3GdHjY GdJbdjOjs